The Thioredoxin-Regulated α-Amylase 3 of Arabidopsis thaliana Is a Target of S-Glutathionylation - Gurrieri, Libero; Distefano, Luca; Pirone, Claudia; Horrer, Daniel; Seung, David; Zaffagnini, Mirko; Rouhier, Nicolas; Trost, Paolo; Santelia, Diana; Sparla, Francesca (Frontiers in Plant Science, 2019)
Reactive oxygen species (ROS) are produced in cells as normal cellular metabolic by-products. ROS concentration is normally low, but it increases under stress conditions. To stand ROS exposure, organisms evolved series of responsive mechanisms. One such mechanism is protein S-glutathionylation. S-glutathionylation is a post-translational modification typically occurring in response to oxidative stress, in which a glutathione reacts with cysteinyl residues, protecting them from overoxidation. α-Amylases are glucan hydrolases that cleave α-1,4-glucosidic bonds in starch. The Arabidopsis genome contains three genes encoding α-amylases. The sole chloroplastic member, AtAMY3, is involved in osmotic stress response and stomatal opening and is redox-regulated by thioredoxins. Here we show that AtAMY3 activity was sensitive to ROS, such as H2O2. Treatments with H2O2 inhibited enzyme activity and part of the inhibition was irreversible. However, in the presence of glutathione this irreversible inhibition was prevented through S-glutathionylation. The activity of oxidized AtAMY3 was completely restored by simultaneous reduction by both glutaredoxin (specific for the removal of glutathione-mixed disulfide) and thioredoxin (specific for the reduction of protein disulfide), supporting a possible liaison between both redox modifications. By comparing free cysteine residues between reduced and GSSG-treated AtAMY3 and performing oxidation experiments of Cys-to-Ser variants of AtAMY3 using biotin-conjugated GSSG, we could demonstrate that at least three distinct cysteinyl residues can be oxidized/glutathionylated, among those the two previously identified catalytic cysteines, Cys499 and Cys587. Measuring the pKa values of the catalytic cysteines by alkylation at different pHs and activity measurement (pKa1 = 5.70  0.28; pKa2 = 7.83  0.12), we showed the tendency of one of the two catalytic cysteines to deprotonation, even at physiological pHs, supporting its propensity to undergo redox post-translational modifications. Taking into account previous and present findings, a functional model for redox regulation of AtAMY3 is proposed.